Performance of a pilot-scale nitrifying trickling filter treating municipal aerated lagoon effluent - Coats, Erik R (Water environment research : a research publication of the Water Environment Federation, 2015)
Colfax, WA, operates an aerated lagoon to achieve compliance with its National Pollutant Discharge Elimination System (NPDES) permit, which currently requires biochemical oxygen demand (BOD) and total suspended solids (TSS) removal. However, ammonia removal may soon be required, and Colfax is considering a nitrifying trickling filter (NTF) that would allow them to also maintain the lagoons. To obtain data from which to ultimately design a full-scale system, a four-year NTF pilot study was performed. Results demonstrated that an NTF would be an effective, reliable NH3 removal method and could produce effluent NH3 concentrations < 1.0 mg/L. NTF performance was characterized by zero- and first-order kinetics; zero-order rates correlated with influent NH3 concentrations and mass load. Utilizing data from these investigations it was determined that the pilot NTF could be reduced by 19%, which demonstrates the value of pilot testing. Finally, pilot data was evaluated to provide a data set that will be useful to engineers designing full-scale NTFs